Electoral manipulation via expenditure composition theory and evidence - Drazen, Allan 1950-; Eslava, Marcela 1975- (National Bureau of Economic Research, 2005)
"We present a model of the Political Budget Cycle in which voters and politicians have preferences for different types of government spending. Incumbents try to influence voters by changing the composition of government spending, rather than overall spending or revenues. Rational voters may support an incumbent who targets them with spending before the election even though such spending may be due to opportunistic manipulation, because it can also reflect sincere preference of the incumbent for types of spending voters favor. Classifying expenditures into those which are targeted to voters and those that are not, we provide evidence supporting our model in data on local public finances for all Colombian municipalities. Our findings indicate both a pre-electoral increase in targeted expenditures, combined with a contraction of other types of expenditure, and a voter response to targeting"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Elections -- Economic aspects -- United States -- Econometric models; Government spending policy -- United States; USA